A New Model of Bone Remodelling - Justyna MIODOWSKA; Jan BIELSKI; Magdalena KROMKA-SZYDEK (Engineering Transactions, 2016)
The objective of this paper is to propose a mathematical model of bone remodelling, including underload and overload resorption, equilibrium and bone grow states which can occur during healing process. A continuous function of bone density rate vs. mechanical stimulus is proposed. The created model is used to predict the stress-stimulated change in callus density. It is an extension of mathematical descriptions available in literature.